Understanding Connectivity of Settlements: Implications of the Power Curve - Seeman, Kurt; Marinova, Dora (Modelling and Simulation Society of Australia and New Zealand, 2009)
Research on human settlements has traditionally focussed on one or a few descriptive or functional aspects, such as geographical characteristics of the locality, the economy, housing, transport, infrastructure, education or health, or created models with varying degrees of complexity that attempt to bring these elements together. This paper applies a different approach that is based in understanding connectivity within and between complex systems. It outlines a new growth area for settlement research and design which brings into play the concept of scale-free hierarchical networks with preferential tendencies, best described by the power curve. Using examples ranging from remote communities to developing countries, the concept helps explain among others, the economic connectivity within a globalised world. The paper also argues that understanding the implications of connectivity is a step towards predicting, evaluating and diagnosing the social, cultural and economic sustainability of settlements.